Arabic Loanwords Integration in Indonesian Madrasah Education: Analysis of Pedagogical Effectiveness and Cross-Linguistic Transfer - Muhammad Afifudin Dimyathi; Junaedi Junaedi; Syaifuddin Syaifuddin; Ali Mas’ud (Nazhruna: Jurnal Pendidikan Islam, 2025)
This study examines the integration of Arabic loanwords into Indonesian madrasah education through a mixed-methods analysis. With 2,000-3,000 documented Arabic loanwords in the Indonesian lexicon, these borrowings offer unique pedagogical potential. The research employed a convergent parallel Design with 147 students and 15 teachers across six Madrasah Tsanawiyah in Surabaya, utilizing questionnaires, interviews, and textbook analysis. Content analysis identified 412 Arabic loanwords across grades 7-9 textbooks (18.7% of the vocabulary corpus), with religious vocabulary at 62%, everyday vocabulary at 34%, grammatical terms at 16%, and environmental vocabulary at 12%. Student recognition patterns showed religious vocabulary highest (88%), followed by everyday (65%), grammatical (48%), and abstract vocabulary (37%). Overall, 78% reported enhanced learning confidence and 84% improved comprehension, with strong multimedia preference (90%). However, 15% experienced semantic confusion when Indonesian meanings diverged from Arabic contexts. Teachers universally recognized the pedagogical value of loanwords, employing comparative linguistic analysis, multimedia integration, and contextual reinforcement strategies. Challenges included semantic drift (50%), grammatical complexity regarding gender distinctions (37.5%), and time constraints. The study recommends enhanced contrastive linguistic analysis in teacher preparation, etymology-based supplementary modules, and standardized loanword pedagogy approaches for Indonesian madrasah contexts.